Brush Your Hair, Medusa! - Holub, Joan; Patricelli, Leslie (New York : Abrams Appleseed, 2015)
An illustrated, easy-to-read retelling of the Greek myth of Medusa, whose refusal to allow her hair to be brushed could have dire consequences.
Keywords: Medusa (Greek mythology) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Medusa (Greek mythology) -- Fiction; Mythology, Greek -- Fiction